Motivasi Mahasiswa Dalam Bidang Enterpreneurship Selama Masa Pandemic Covid-19 - Depi Anggraeni; Nadia MA; Khusnul Khotimah; Rahayu Hamidah; Silvie Mil (JURNAL ABDIMAS SERAWAI, 2022)
The current COVID-19 pandemic is one of the real threats and challenges for the business world, not only in certain regions but all entrepreneurs globally. Therefore, this entrepreneurship can be done by anyone including students who can participate in improving the low economy, so this becomes a challenge for students in developing their field in the field of entrepreneurship. Through the PKM program held by the Uhamka PK2M team, students are trained to learn entrepreneurship by being given various facilities such as business capital in the form of grants, entrepreneurship training and business assistance. Student assistance is carried out by the accompanying lecturer for each business group team. Entrepreneurship program for students aims to increase students' motivation and entrepreneurial attitude. Business assistance to students in doing entrepreneurship can increase students' motivation and attitudes in working to run a business